Enhancing Data Backup and Recovery in Cloud Computing with Secure Database Monitoring - Mehul Pawar; Phapale, Anuja S. (International Journal of Applied and Advanced Multidisciplinary Research, 2023)
The company uses unregistered data to improve performance, but this comes at the cost of limited backup options, data loss, and a voluntarily damaging week-long downtime. Even if they have backup systems, they cannot meet the SLA recovery time. To solve these problems, this work presents a secure database monitoring method for cloud computing. This approach adjusts the backup speed according to the data volume; This is important when data grows at least 30% per year. For the some companies, the data doubles every 3-4 years or more and SLAs and recovery targets need to be updated. At the same time, business needs for data recovery continue to grow, highlighting the need for more robust and responsive data management strategies.